2019
DOI: 10.32604/jrm.2019.06286
|View full text |Cite
|
Sign up to set email alerts
|

ZnSe Nanoparticles Reinforced Biopolymeric Soy Protein Isolate Film

Abstract: ZnSe nanoparticles have been synthesized by microwave assisted method by using zinc chloride, selenium powder and ethylene diamine. The synthesized nanoparticles have been characterized structurally by FT-IR and XRD as well as morphological characterization was done by scanning electron microscope (SEM). The crystallite size after synthesis was obtained around 30 nm for pure ZnSe nanocrystallites. However, from SEM micrograph, agglomerated ZnSe nanoparticles of irregular shapes were observed. The assynthesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…These results implied that the CNF and ZnO NPs were engrafted into the amide bonds of gelatin molecular chains via a conjugation process (Hosseini et al., 2015). By the incorporation of CNF and ZnO NPs, the broadness of the peak between 3,000 and 3,600 cm −1 decreased, signifying a decrease in hydrophilicity of gelatin films (Kumar et al., 2019). The N–H stretching of the amide‐A band has transferred from 3,400 cm −1 for gelatin film to 3,443 cm −1 for G/CNF/ZnO NPs film.…”
Section: Resultsmentioning
confidence: 99%
“…These results implied that the CNF and ZnO NPs were engrafted into the amide bonds of gelatin molecular chains via a conjugation process (Hosseini et al., 2015). By the incorporation of CNF and ZnO NPs, the broadness of the peak between 3,000 and 3,600 cm −1 decreased, signifying a decrease in hydrophilicity of gelatin films (Kumar et al., 2019). The N–H stretching of the amide‐A band has transferred from 3,400 cm −1 for gelatin film to 3,443 cm −1 for G/CNF/ZnO NPs film.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporating reinforcing agents is also a very promising path to improve the mechanical properties of soy protein based materials. It has been reported that fibers, 17 nanoclay, 18 nanocrystals, 19 silica, 20 POSS, 21 carbon nanoparticles, 22 modified protein particles, 23 and ZnSe nanoparticles, 24 and so forth have been incorporated into soy protein to improve the mechanical properties. The polar groups on soy protein macromolecules could produce strong interactions with these particles, and these interactions were influenced by processing conditions such as pH values by changing the secondary structure and surface charges of soy protein globulin 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Incorporating fillers is an effective method to improve the mechanical performance of polymeric materials. [8] It has been reported that nanoclays, [9] fibers, [10] carbon nanotubes, [11] and so forth. have been incorporated into foam materials to improve the physical properties of the resulting foams.…”
Section: Introductionmentioning
confidence: 99%